Swimming in the dark : a novel - Jedrowski, Tomasz (William Morrow an imprint of Harper Collins Publishers, 2020)
When university student Ludwik meets Janusz at a summer agricultural camp, he is fascinated yet wary of this handsome, carefree stranger. But a chance meeting by the river soon becomes an intense, exhilarating, and all-consuming affair. After their camp duties are fulfilled, the pair spend a dreamlike few weeks camping in the countryside, removed from society and its constraints, Ludwik and Janusz fall deeply in love. But in their repressive communist and Catholic society, the passion they share is utterly unthinkable. Once they return to Warsaw, the charismatic Janusz quickly rises in the political ranks of the party and is rewarded with a highly-coveted position in the ministry. Ludwik is drawn toward impulsive acts of protest, unable to ignore rising food prices and the stark economic disparity around them. Their secret love and personal and political differences slowly begin to tear them apart as both men struggle to survive in a regime on the brink of collapse.